The Criminalization of Verbal Sexual Harassment in Amending Macao's Criminal Code - Yang, Vincent (Socioeconomic Development Research, 2016)

Social Impact Assessment: The Case of The Cradle of Hope Association in Macau - Vendramini, Marjory Rangel De Faria (University of Saint Joseph, 2016)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Development of Structure and Sensitivity of the Fish Inner Ear - Vasconcelos, Raquel O.; Alderks, Peter W.; Sisneros, Joseph A. (Fish Hearing and Bioacoustics: An Anthology in Honor of Arthur N. Popper and Richard R. Fay, 2016)
Fish represent the largest group of vertebrates and display the greatest diversity of auditory structures. However, studies addressing how the form and function of the auditory system change during development to enhance perception of the acoustic environment are rather sparse in this taxon compared to other vertebrate groups. An ontogenetic perspective of the auditory system in fishes provides a readily testable framework for understanding structure–function relationships. Additionally, studying ancestral models such as fish can convey valuable comparable information across vertebrates, as early developmental events are often evolutionary conserved. This chapter reviews the literature on the morphological development of the fish auditory system, with particular focus on the inner ear structures that evolve from an otic placode during early embryonic development and then continue to undergo differentiation and maturation in the postembryonic phase. Moreover, the chapter provides a systematic overview of how auditory sensitivity develops during ontogeny. Although most studies indicate a developmental improvement in auditory sensitivity, there is considerably species-specific variation. Lastly, the paucity of information and literature concerning the development of auditory capabilities for social communication in fishes is also discussed. Further investigation on the development of structure and function of the fish auditory system is recommended in order to obtain a deeper understanding of how ontogenetic morphological changes in the auditory pathway relate to modifications in acoustic reception, auditory processing, and the capacity to communicate acoustically.
Keywords: Auditory development; Auditory physiology; Ear morphology; Fish ontogeny

Listening to the Environment: Importance of Early Acoustic Experience on Hearing and Development in Zebrafish - Vasconcelos, Raquel (University of Saint Joseph, 2016)

The vocal brain of fish: development of auditory processing and vocal motor control - Vasconcelos, Raquel (University of Saint Joseph, 2016)

A Financial Valuation Study of AT&T, Inc - U, Weng Kei (University of Saint Joseph, 2016)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

City guide publications shift towards digital platform a case study in Macau - U, Sou Mui (University of Saint Joseph, 2016)
Keywords: City planning; Macau; Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

The relationship between children's attachment with parents and general self-efficacy during young adulthood in Macau - U, Lei Fong (University of Saint Joseph, 2016)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Feasibility study of a living lab in Macau for the creative industries - Tong, Pui Si (University of Saint Joseph, 2016)
Keywords: Creative ability in business; Macau; Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

The relationship between time perspective and study motivation on decision making of student in Macau - Tong, I Wan (University of Saint Joseph, 2016)
Keywords: Thesis and Dissertations Master of Counselling and Psychotherapy (MCP); University of Saint Joseph

Learning Computer Science: Dimensions of Variation Within What Chinese Students Learn - Thota, Neena; Berglund, Anders (ACM Transactions on Computing Education, 2016)
We know from research that there is an intimate relationship between student learning and the context of learning. What is not known or understood well enough is the relationship of the students’ background and previous studies to the understanding and learning of the subject area—here, computer science (CS). To show the contextual influences on learning CS, we present empirical data from a qualitative investigation of the experiences of Chinese students studying for a master degree at Sweden's Uppsala University. Data were collected of the students’ understanding and learning of CS, their experience of the teaching and their own studies, and of their personal development in Sweden. Using an analysis framework grounded in phenomenography, we analytically separated the what and how aspects of learning. In this article, we describe the what, or the content of the students’ learning, and identify dimensions of variation in the experiences of students. These dimensions relate to the foci of the CS programs, the learning outcomes, and the impact of the studies. The findings from the analyses indicate pedagogical and pragmatic implications for teaching and learning CS in higher education institutions. The study extends the traditional use of phenomenography through the discussion of the dimensions of variation in the experiences and the values within the dimensions. It opens the way for understanding the relational nature of learning in computing education.
Keywords: Computer science education; context; phenomenography; qualitative research; variation theory

E2S Enso entertainment strategies a business plan - Steinen, Jesko von den (University of Saint Joseph, 2016)
Keywords: Business planning; Macau; Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Drug abuse among adolescents in Macau: its psycho-socio-cultural perspectives - Song, Yi Xuan (University of Saint Joseph, 2016)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Korean memorial service for the dead: a re-evaluation of the Christians' understanding - Song, Jeongmin (University of Saint Joseph, 2016)
Keywords: Thesis and Dissertations Master of Religious Studies (MRS); University of Saint Joseph

A Diocese de Macau no alvorecer da Diocese de Dili - Soares, Domingos da Silva (University of Saint Joseph, 2016)
Keywords: Thesis and Dissertations Master of Religious Studies (MRS); University of Saint Joseph

Espaço, história e memória: os potiguara na paraíba - Simoes, José Manuel (Sæculum – Revista de História, 2016)
últimos assumidos remanescentes provavelmente de um território cultural antes bem mais vasto vivem atualmente nos municípios de Baía da Traição, Marcação e Rio Tinto, no litoral setentrional da Paraíba - nem sobre s seus espaços, culturas e gentes. É preciso dobrar a primeira metade do século XX para se encontrar nos títulos gerais de histórias da Paraíba alguma atenção pelos Potiguara e a sua movimentação histórica no processo longo e contraditório de formação da capitania e da instalação portuguesa na região, enfrentando primeiro a concorrência comercial e militar francesa, depois no século XVII a ocupação holandesa e sempre, até quase meados de seiscentos, a oposição muitas vezes feroz e brutal de vários grupos e milícias potiguaras. A arqueologia confirma um processo recente de formação histórica dos espaços atualmente reivindicados como originais e tradicionais pelos Potiguara. Os estudos linguísticos disponíveis sobre os Potiguara também não destacam a memória rigorosa de um espaço cultural arcano e pré-colonial. Os espaços Potiguara de hoje com este sistema de organização agrícola quase binário são tudo menos naturais. Trata-se, antes, de um espaço em recorrentes transformações históricas, demográficas, económicas e sociais que desafia qualquer ideia de um espaço ‘natural’, ‘original’ ou ‘essencial’ dos Potiguara. Seja como for, estas polarizações estruturais são historicamente aquelas que presidiram à exata produção dos espaços que atualmente os Potiguara apresentam como seus, originais, antigos e tradicionais seguindo, afinal, um modelo colonial de ocupação de espaços e especialização das gentes do Brasil.
Keywords: História colonial

Spatial modulation of the hydrological risk at Praia, Cape Verde - Silva, José Lino; Neves, Ana Cristina; Negreiros, João Garrott Marques (IOP Conference Series: Earth and Environmental Science, 2016)
Hydrology modeling became a relevant topic for the Cidade da Praia, Cabo Verde, Africa, due to negative impact risk to local population and its assets. The modeling via Geographical Information Systems (GIS) can help the decision-making process of space occupation and characterization for this type of risk. Under the municipalities of Praia, the phenomenon of flash flood is common, causing soil erosion and landslide. This constitutes a risk for the local habitat, particularly in districts with a lack of strong human infrastructures. To simulate, analyze and generate risk maps using GIS to help this county governance authorities for decision-making, thus, becomes the main aim of this article.

Catholic social teaching and environmental responsibility - Rothlin, Stephan; McCann, Dennis (A planetary and global ethics for climate change and sustainable energy, 2016)

International Business Ethics: Focus on China - Rothlin, Stephan; McCann, Dennis (Springer-Verlag, 2016)
This book addresses an essential need felt by many who seek to promote best business practices in China and East Asia – namely the need for culturally appropriate instructional materials (basic information, case studies and ethical perspectives) that will allow managers and entrepreneurs to understand and embrace the challenge of moral leadership in business. In an era characterized by globalization and the increasing importance of the economies of China, India, Japan and SE Asia, international business ethics must reflect the concerns of the people living and working in this area, the moral and spiritual traditions that have nurtured them and their specific contributions to sustainable development. This book presents twenty important case studies, taken from newsworthy events of the past few years, in which Asians and others have attempted to respond to this challenge. Each case study has been selected and shaped in order to highlight various aspects of doing business in Asia, starting with basic principles and moving on to the specific responsibilities that businesses have towards their various stakeholders. The authors contend that the best way to appreciate the relevance of Asian moral and spiritual traditions is to determine their specific contribution to virtue ethics, where the ancient traditions of both East and West converge in their focus on the qualities of moral leadership that form the basis of best business practice. Exploring the case studies will enable readers to appreciate the continued relevance of these ethical perspectives in Asian business. Best business practice clearly involves learning to do business and playing the game according to the rules; but the necessity of playing by the rules is not likely to become clear until one takes up the path that leads to a virtuous life in business, developing a moral character chiefly based on integrity.

Import and sales of Chinese fabrics in Brazil: a feasibility study - Ribeiro, Lucas Rodrigues Gomes (University of Saint Joseph, 2016)
Keywords: Brazil; China; Textile fabrics; Textile fabrics Markets; Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Attitudes towards counseling between iran and Macau universities students - Rashinia, Jafar (University of Saint Joseph, 2016)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Mesozoic Granitic Magmatism in Macao, Southeast China - Quelhas, P. M.; Mata, J.; Lou, U. T.; Ribeiro, M. L.; Dias, Ágata (AGU Fall Meeting Abstracts, 2016)
Macao ( 30 Km2) is a territory characterized by small granitic intrusions, located along the coastal region of Southeast China (Cathaysia Block). Granitoids occur as different facies, including microgranite dykes, with distinct textural, mineralogical and geochemical features, for which a middle-upper Jurassic age ( 164 Ma) has been proposed. New data suggest that these granitoids are mostly high-K calc-alkaline metaluminous (A/CNK = 0.8 - 1.1) biotite granites, consistent with total absence of primary muscovite. They show variable amounts of SiO2 (67-77%), reflecting different degrees of magmatic evolution. There is also variability in terms of trace elements, particularly Rare Earth Elements (REEs), evidenced by decreasing (La/Sm)N, (Gd/Lu)N, (Ce/Yb)N and (Eu/Eu*)N towards the more evolved samples, which can be partly attributed to fractional crystallization processes. Most of the granitoids are characterized by (La/Yb)N = 3 - 10.8, showing negative Ba, Nb, Sr, Zr, P, Ti and Eu anomalies. On the other hand, microgranite dykes, along with a few more evolved granites, show an opposite tendency, being usually enriched in HREEs relatively to LREEs with (La/Yb)N = 0.4 - 1.1. Our data suggests intermediate genetic affinities between I-type and A-type granites. Although these granitoids are mostly metaluminous (characteristic of I-types), Ga/Al ratios, usually used to identify A-types, are close to the accepted boundary between A-type and other granite types. The affinities with A-type granites are more marked for the more evolved facies, which depict higher values of FeOt/MgO (14 - 60) and K2O/MgO (60 - 250). Their trace element characteristics are also transitional between WPG (Within-plate granites) and Syn-COLG (Collision Granites). We interpret those transitional characteristics (A/I and WPG/Syn-COLG) of Macao granitoids as reflecting an origin by melting of infracrustal sources over a period of high heat transfer from mantle to crust during an extensional tectonic setting probably contemporaneous with the subduction of the paleo-Pacific plate beneath the Eurasia, whose paleo-suture is thought to be located in the east flank of the Central Range, Taiwan.
Keywords: 8499 General or miscellaneous; VOLCANOLOGY

Financial valuation of Pfizer Inc - Pires, Rui Carlos Moreno (University of Saint Joseph, 2016)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Historical Space in Macao - Pinheiro, Francisco Vizeu (IACM : Jiangnam University, 2016)

Viability of recycling ventures in Macau - Okorocha, Anthony Ifeanyi (University of Saint Joseph, 2016)
Keywords: Macau; Recycling industry; Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Biased performance prediction and estimate: concurrent examination of the optimistic bias and miscalibration of performace judgment - Ngan, Henrique Fátima Boyol (University of Saint Joseph, 2016)
Kruger and Dunning (1992) found that unskilled people were typically unaware of their own performance and ability. In this context, unskilled performers were shown to overestimate their performance and ability, whereas skilled performers often accurately predicted their own performance and ability. Such miscalibration in self-assessment is usually attributed to a lack of so-called metacognitive skills necessary for performance evaluation. However, it remains unknown to what extent the miscalibration of performance judgment and optimistic bias is observed in the Chinese culture. This thesis examines patterns of miscalibration of performance judgment and specific optimistic bias. This thesis also builds on a range of previous studies of performance judgment and optimistic bias. In order to investigate the performance judgment and optimistic bias in this context, two studies were conducted as part of the research aspect of this thesis. In the first study, participants were given a reasoning task on which they had to predict their performance before completing the task and estimate their performance upon completion of the task. The second study followed similar methodology, with two additional tasks – Institute For Tourism Studies (IFT) module and the respective midterm examination. Results from both studies indicate that biases in performance judgment occur in the Chinese culture, and may yield negative consequences to those persons who exhibit such judgments. Although metacognitive ability provides some explanation for the miscalibration of performance judgment, the results of the current study indicate that task optimistic bias provides another, equally viable explanation for the miscalibration of performance judgment. The findings presented in this thesis suggest that inaccurate judgments of performance occur within various domains (general and specific iii performance contexts) and that there are a range of implications associated with these biases. Keywords: Miscalibration of performance judgment, optimistic bias, absolute optimistic bias, comparative optimistic bias, overestimation, overplacement, underestimation, underplacement
Keywords: Thesis and Dissertations PhD in Psychology (D-PSY); University of Saint Joseph

Valuing Walt Disney Co - Neves, Júlio Alexandre Dias (University of Saint Joseph, 2016)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

An exploratory study of Chinese rituals in street shops in Macau - Moreira, Irene Mitsiko Sadoyama (University of Saint Joseph, 2016)
Keywords: Business ethics; China; Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

The Post-Colonial Imaginary & Politics of Representation in the Macao SAR: The TEATRAU (Theatre showcase from Portuguese-speaking countries) & the (Re) emergence of 'Lusofonia' under Chinese stars - Morais, Isabel (Theatre 15 China, India & the Eastern World, 2016)

Baptism as Christian Initiation in the New Testament - MONERA, A. (Orientis Aura, 2016)

The evaluation of Microsoft Corporation - Mendonça, César (University of Saint Joseph, 2016)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Financial valuation of Shun Tak Holdings - Magalhães, João Pinto de (University of Saint Joseph, 2016)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Assessing Driving Behavior in Public Transportation through Mobile Crowd Sensing: A Concept Proposal for Macau Public Transportation System - Ma, Fa Chun; Tóng, Sok Hán; Cordeiro, João (2016 10th International Conference on Innovative Mobile and Internet Services in Ubiquitous Computing (IMIS), 2016)
This paper introduces a concept proposal for accessing driving behavior in public transportation through Mobile Crowd Sensing (MCS), as part of a long-term research project on Advanced Public Transportation System (APTS). The proposed concept makes use of mobile device's accelerometer and passengers' qualitative evaluation to identify aggressive driving behavior, which is believed to be a major factor for unnecessary accidents and fuel consumption. A survey and comparison of IT services (mobile applications and websites) provided by Macau Government and private bus companies in Macau, regarding bus-related information, such as fares, routes and route diversions is also provided.

The impact of social support on the mental health of the visually impaired in Macao = 社會支援對於澳門視障人士的心理影響 - Loi, Wai Cheng (University of Saint Joseph, 2016)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

A financial valuation of Wynn Resorts Limited - Li, Iok I. (University of Saint Joseph, 2016)
Keywords: Financial institutions Valuation; Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph; Wynn Resorts Limited

A financial valuation of Tencent Holdings Limited - Leong, Weng Hong (University of Saint Joseph, 2016)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A financial evaluation of MGM Resort International - Lei, Pou I. (University of Saint Joseph, 2016)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Asia-Europe Comparative Studies Research Project(AECSRP) - Leandro, F. J (University of Saint Joseph, 2016)

Employees’ Dissonance in non-gaming industries A Casino Dominant Econom - Kuok, A.C.H. (2016 Global Conference of Education and Psychology, 2016)

Extending social networking into the secondary education sector - Kio, Su Iong (British Journal of Educational Technology, 2016)
Secondary schools do not have the same technical resources and capabilities as universities. They usually need to rely on ready-to-use tools to fulfill their information and communication technology (ICT) structure. Social networking site (SNS) has emerged as a practical solution to this need. However, few have collected empirical data on the application of SNS in a secondary school setting. This paper probes into the current condition of SNS usage among secondary school students using a sample of 851 students in Macau, a Special Administrative Region (SAR) of China. Data in terms of access, profile and activities are collected. The activities on SNSs are analyzed by regression techniques to produce a prediction model relating perceived academic benefit and SNS activities. The model yields a strong positive relationship between that benefit and activities such as raising questions and engaging in study-related discussions. The model also yields a weak dependency on activities such as searching for information and entertainment. The paper also evaluates the actual academic utilization of a Facebook Group for one class of secondary school students for a period of one year. At the end of the year, various opinion parameters are measured, and improvements are observed in most parameters.

The challenges of ethnic foodservices business in Macau: an Indian restaurant case study - Khan, Muhammad Imran (2016)
Keywords: Food service management; Macau; Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

ARCASIA Roundtable on Architectural Education in Asia - Future Chalenges and Visions - Jay Ho (Architecture Macau Magazine, 2016)

An exploratory investigation into success factors of e-commerce in Macau - Hoi, Ka Leng (University of Saint Joseph, 2016)
Keywords: Electronic commerce; Macau; Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Exploring occupational stress and job satisfaction among pharmacists in Macau - Ho, Joel (University of Saint Joseph, 2016)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Introducing A Blended Learning Environment to Enhance Student Academic Efficacy - Ho, Io Weng (University of Saint Joseph, 2016)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Behavioral plasticity meets neuroplasticity: brain neurogenesis in the polymorphic fish Salaria pavo - Gonçalves, David Manuel Flores (University of Saint Joseph, 2016)

Vatican II - Gomez, Fausto (Orientis Aura: Macau Perspectives In Religious Studies, 2016)
From a reason-faith perspective, I reflect on “Vatican II: Gaudium et Spes Fifty Years Later.” In the introduction, I speak briefly on the Second Vatican Council, and on its Pastoral Constitution Gaudium et Spes (“Joy and Hope”) and its ethical and social teachings.

Education in Religious Freedom - Gassner, Franz (Orientis Aura: Macau Perspectives in Religious Studies, 2016)
The author emphasizes the crucial relevance of religious liberty and freedom of expression for a harmonious and peaceful development of modern societies. He follows the prophetic Declaration of Religious Freedom of Second Vatican Council (1965) with its constitutional limitation of governmental powers in matters of religion. The high value of religious freedom is judged as bulwark of all human rights and true capstone of sound human and societal developments, which have to be guarded against any form of infringements. In this regard, a reasonable education in religious freedom and liberty is indispensable for young people of the twenty-first century. Education in religious freedom in the context of moral and religious formation is based on the dignity of every human person and promotes a deeper mutual and cultural understanding by respecting the conscience of every human person. It thus carries the potential to diminish conflicts and clashes in a sustainable way. Educational reforms in countries have to include the high value of religious liberty and freedom as a main element and condition for human dignity and a peaceful global development.

Education in Religious Freedom: Path to Peace and Stability - Gassner, Franz (Orientis Aura, 2016)

Relationship between Traditional Chinese Beliefs about Aetiology of Mental Disorders and Help Seeking: A Survey of the Elderly in Macao - Found, A. (East Asian Archives of Psychiatry: Official Journal of the Hong Kong College of Psychiatrists = Dong Ya Jing Shen Ke Xue Zhi: Xianggang Jing Shen Ke Yi Xue Yuan Qi Kan, 2016)
OBJECTIVE: A wide range of factors can influence help-seeking attitudes when individuals experience a mental disorder. The current study investigated the relationship between traditional Chinese beliefs related to the aetiology of mental disorders and help-seeking attitudes among elderly participants in Macao. METHODS: In order to ensure the suitability of participants for inclusion in this study, the participants were required to complete an initial screening test using the Short Portable Mental Status Questionnaire (SPMSQ). Participants who successfully passed the test (n = 183) completed a questionnaire that included the Inventory of Attitudes Toward Seeking Mental Health Services (IASMHS), a set of 9 items related to traditional Chinese beliefs about aetiology of mental disorders and demographic items. RESULTS: The IASMHS scores were higher for female participants and for participants who had completed high school compared with those who had never attended school or who had only completed primary education. Endorsement of traditional Chinese beliefs about the aetiology of mental disorders was higher for male participants. There was a negative correlation between traditional Chinese aetiology beliefs related to mental disorders and help-seeking attitudes. CONCLUSION: Traditional Chinese beliefs related to the aetiology of mental disorders are a negative factor that inhibits help seeking. Implications for efforts to increase the utilisation of mental health services by the elderly are discussed.
Keywords: Aged; Asian People; Asian continental ancestry group; Cultural Characteristics; Female; Health Knowledge, Attitudes, Practice; Help-seeking behavior; Humans; Macau; Male; Mental Disorders; Mental disorders / etiology; Patient Acceptance of Health Care

Improving social skills of primary school students through a social skill enhancement program - Fok, Ka Ian (University of Saint Joseph, 2016)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Wrestling with God - Flores, Randolf (Orientis Aura: Macau Perspectives In Religious Studies, 2016)
This study will discuss the following Old Testament texts: Gen 32:23-32; Jon 1:17; Tob 6:1-9; and Exod 4:24-26 and will argue that these are about the initiation of a person to do a divine mission. Some parallels from Asia—Epic Gilgamesh, texts from Tibetan Buddhism, Hinduism, and the Philippine epic, Biag ni Lam-ang will also be taken into consideration to shed light on them. It will also present their interpretation as typoi of the sacraments of initiations found in early Christian literature and art.

Music training influences on brain development and as a tool for learning improvement - Ferreira, Ana Filipa Neves (University of Saint Joseph, 2016)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Maximizing verbal communication in English amongst Macau Chinese secondary students in private tutorial sessions - Fernandes, Keith Otteran Reis (University of Saint Joseph, 2016)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Feasibility study of a digital gourmet marketplace in Hong Kong - Farinha, João Pedro (University of Saint Joseph, 2016)
Keywords: Google; Hong Kong; Marketplaces; Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A survey of independent art galleries in Macao: analysing organisational,curatorial and promotional strategies under service design framework - Dias, Ana Cristina Ferreira (University of Saint Joseph, 2016)
Keywords: Art galleries, Commercial; Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Petrology and Geochemistry of Granitic Rocks from Macao - Dias, Ágata; Quelhas, P; Lou, U; Mata, J; Ribeiro, M L (Goldschmidt, 2016)

Petrology and Geochemistry of Igneous Rocks from Macao: Implications for the Crustal Evolution of Southern China - Dias, Ágata (University of Saint Joseph, 2016)

Aid and poverty reduction: comparing China and France's aid policies and projects in Guinea - Diakité, Ansoumane Douty (University of Saint Joseph, 2016)
The purpose of this research is to analyse the nexus between foreign aid and poverty reduction. In this research, aid provided by traditional and (re)emerging donors, China and France, was compared to understand their strategies toward poverty reduction and the impact of their aid in improving the conditions of their beneficiaries. Guinea, a Least Developed Country, was used as unit of comparison and assessment. Qualitative research methodology was used to collect data about the two aid donors, China and France. Among other research tools used, there are documents’ analysis (official documents from donors and recipients, declarations, scholarly works, media articles, etc.), interviews with various stakeholders, site visits and observation. As for main findings, this research found similarities and differences between China and France’s aid strategies in general and in Guinea in particular. There are similarities in the ways they integrate poverty reduction into their aid policies, motives and partly in their geographical and sectoral allocation systems. In terms of differences, they use different instruments and conditions to deliver their aid for poverty reduction. Regarding the impact of their aid, both donors have to some extent contributed to improving the access of the poor population in Guinea to basic services such as education, health, water and sanitation, etc. Finally, contrary to those who have denied the importance of foreign aid as a financial tool to reduce poverty, this research posits that aid is still a relevant tool to address poverty. However, more work needs to be done at donor, recipient and direct beneficiaries’ levels to ensure its effectiveness. On the other hand, it posits that the divide between traditional and (re)-emerging donors is becoming blurred as their strategies to address poverty are becoming increasingly alike
Keywords: Thesis and Dissertations PhD in Government Studies (D-GS); University of Saint Joseph

Feasibility study into implementation of automated traffic lights to improve emergency vehicle response time in Macau - Chong, Kirl Cheah (University of Saint Joseph, 2016)
Keywords: Emergency vehicles; Macau; Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

The impact of declining gaming revenue in the hospitality industry in Macao - Choi, Mei Chan (University of Saint Joseph, 2016)
Keywords: Hospitality industry; Macau; Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Quality assurance for Macao's higher education institutions: challenges and opportunities - Cheong, Wai San (University of Saint Joseph, 2016)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

A financial valuation of Melco Crown Entertainment Limited - Cheong, Man (University of Saint Joseph, 2016)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Pathway to drug addiction among Macau teenagers - Cheang, Tat Hin (University of Saint Joseph, 2016)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Meetings and conventions in Macao: Challenges and opportunities - Che, Sio Wang (University of Saint Joseph, 2016)
Keywords: Challenges; Macau; Meetings; Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Strategies in vocal warm up - Chan, Wun Ming (University of Saint Joseph, 2016)
Keywords: Thesis and Dissertations Master of Choral Conducting (MCC); University of Saint Joseph

The role of mangroves on the bioaccumulation and citogenotoxic effects of metals and pesticides on the food web of a tropical coastal system - Chan, Shek Kiu; Tagulao, Karen (University of Saint Joseph, 2016)

The Role of Mangroves on the Bioaccumulation and Citogenotoxic Effects of Metals and Pesticides on the Food Web of a Coastal System - Chan, S. K; Tagulao, Karen (University of Saint Joseph, 2016)

The effect of family and personal factors on marital attitudes and expectations in Macau - Chan, Cheng Nga (University of Saint Joseph, 2016)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Design Thinking and Entrepreneurship: In Macanese Corporate Environment - Caldeira, Wilson (University of Saint Joseph, 2016)
Keywords: Entrepreneurship Religious aspects; Macau; Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Relapse prevention: a reflection around high-risk situations, self-efficacy and life-style modifications in substance abusers - Bucho, Marta (University of Saint Joseph, 2016)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

John Alexander Holm (1943-2015) - Baxter, Alan N. (Journal of Pidgin and Creole Languages, 2016)

Implications of cultural values in retail strategies for the gaming industry: Chinese consumer values in the context of Macau - Barbosa, Hong Seng (University of Saint Joseph, 2016)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Analysis of Business Clusters in Macau - Alves, Jose; Trimarchi, Michael (University of Saint Joseph, 2016)

Can the application of neuroscience improve processes for ongoing improvement in organizations? - Alves, José (University of Saint Joseph, 2016)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Career aspirations of generation y: the case of event management graduates in macau - Alves, José (University of Saint Joseph, 2016)
Keywords: China Macau; Marketing; Organizational effectiveness; Planning; Special events; Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Migrant transnationalism and religious transformation: religious faith and practice among Filipino migrants (An Anthroplogical Approach Focusing on Macau) - Alabanza, Ian Shelley Sasha Pugal (University of Saint Joseph, 2016)
Religion and migration are both phenomena that have endured perennially in the experience of humanity. However, studies on the relationship of these two subjects are not as prevalent compared to how widespread international migration has become especially among people coming from religious societies. This work contributes to the knowledge base on the significance of religion within the context of international migration by looking at how religious faith and practice evolve as a result of the experience of migration. Interviews about the migration narratives of Filipino Catholics working in Macau were conducted. These were supported by data collected through the use of survey questionnaires that look into changes in religious practices of respondents as well as their attitudes towards faith and belief. The study has found that there is constancy in the religious faith and practice of Filipino Catholics even amidst external changes to the physical and social environment brought about by moving to a predominantly secular society. Through recourse to anthropological analysis, this immutability of faith is attributable to the unique ethnographic feature of Filipinos’ high regard for the centrality and importance of interiority in their life. Keywords: migration, immigrant religion, faith, Filipino religiosity
Keywords: PhD in Global Studies (D-GLS); Thesis and Dissertations; University of Saint Joseph